A Cost–Benefit Analysis of Summer Reading Programs Implemented Under State Guidelines. Issue 4 (June 2020) - Reed, Deborah K.; Cook, Kevin M.; Aloe, Ariel M.
This study investigated the costs of different summer reading programs and compared costs to the benefits of summer school as a way to avoid retaining students not reading proficiently at the end of third grade. Per pupil costs ranged from US1, 665 to US2, 194. The average cost was US1, 887 (range: US266-US5, 552) with 82% of overall expenses attributable to personnel. Results indicate that offering summer reading programs could save schools across the state a total of between US70.6 million and US75.5 million in expenses related to providing an extra year of school had all eligible students been retained in third grade instead. This equates to about US4 in benefit for every dollar invested in summer programs.